Pyroptosis-immune cell cross talk in asthma: From molecular mechanisms to precision therapeutics - Ni, Feng-Xian; Wang, Hui-Xian; Chen, Pei-Sheng; Huang, Hua-Jing; Chen, Hui-Hui; Huang, Dong-Hui; Jiang, Ze-Bo (Frontiers in Immunology, 2025)
Asthma is a heterogeneous chronic airway disease characterized by complex inflammation. Pyroptosis, a pro-inflammatory form of programmed cell death mediated by gasdermin (GSDM) family proteins, has recently emerged as a critical amplifier of airway inflammation and tissue remodeling in asthma. This review delineates the molecular underpinnings of pyroptosis, focusing on the roles of canonical (e.g., NLRP3-caspase-1) and non-canonical (e.g., caspase-4/5/11) inflammasome pathways, as well as the broader concept of PANoptosis. We elaborate on how the pore-forming activity of GSDMD and other GSDMs facilitates the release of potent pro-inflammatory cytokines (IL-1β, IL-18), driving pathogenic cross talk among structural cells (epithelium), innate immune cells (macrophages, eosinophils, ILC2s), and adaptive immunity. Crucially, we contextualize pyroptosis within distinct asthma endotypes, proposing that allergen-driven, NLRP3-dominated pathways may underpin Th2-high/eosinophilic inflammation, while pollutant/viral-triggered, non-canonical/AIM2 pathways may favor Th2-low/neutrophilic phenotypes. The translational potential of targeting pyroptosis is underscored through a discussion of biomarkers (e.g., GSDMD-N, IL-18) and a comprehensive summary of preclinical and early clinical inhibitors targeting NLRP3, GSDMD, and key cytokines. By synthesizing these multifaceted roles, this review posits that a nuanced understanding of pyroptosis networks holds significant promise for pioneering endotype-specific therapeutic strategies in asthma management.